Sentiment Analysis to Understand the Perception and Requirements of a Plant-Based Food App for Cancer Patients. (27th January 2023) - Dalayya, Shekinah; Elsaid, Salma Tamer Fathy Ahmed; Ng, Kher Hui; Song, Tien Lii; Lim, Joanne Bee Yin
Abstract : Understanding human perception and requirements on food for cancer prevention and condition management is important so that food applications can be catered to cancer patients. In this paper, web scraping was conducted to understand the public's perception, attitude, and requirements related to a plant-based diet as a recommended diet for cancer prevention and condition management. Text and sentiment analyses were carried out on results gathered from 82 social sites to determine whether noncancer and cancer patients use plant-based diets, how they have been consumed, their benefits in the prevention and condition management of cancers, the existing myths/fake news about cancer, and what do cancer patients need in a food app. The results of the text analysis highlighted gaps in existing apps, including a lack of credibility as there were a lot of fake news and myths about cancer and endorsement by professionals. Future food apps should provide personalized diets to include both plant-based diets as well as meat, symptom management, good user experience, credibility, and emotional and mental health support.